2003
DOI: 10.1046/j.1471-4159.2003.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine trapping causes the persistent desensitization of α4β2 nicotinic receptors expressed in oocytes

Abstract: To determine whether prolonged nicotine exposure persistently inactivates rat a4b2 nicotinic receptors expressed in Xenopus oocytes, we measured the voltage-clamped a4b2 response to acetylcholine (ACh) before and 24 h after, 1-h or 12-h incubations in 10 lM nicotine. A 12-h incubation in 10 lM nicotine depressed the a4b2 ACh response for 24 h without affecting total or surface a4b2 expression. To determine whether oocyte-mediated nicotine release caused this depression, we co-incubated an a4b2-expressing oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…This effect opposes the actions of those variants on receptor assembly in the absence of nicotine. A confounding factor comes from the observation that X. laevis oocytes act as "nicotine sponges" during incubation with nicotine and release desensitizing concentrations of nicotine into superfusion buffer during recording (Jia et al, 2003). However, HS and LS forms of a4b2 nAChRs do not differ in their sensitivity to steady-state desensitization with subactivating concentrations of nicotine (Marks et al, 2010), so any differences in function observed after 24-hour nicotine across the a4 variants are due to effects conferred by the variants themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This effect opposes the actions of those variants on receptor assembly in the absence of nicotine. A confounding factor comes from the observation that X. laevis oocytes act as "nicotine sponges" during incubation with nicotine and release desensitizing concentrations of nicotine into superfusion buffer during recording (Jia et al, 2003). However, HS and LS forms of a4b2 nAChRs do not differ in their sensitivity to steady-state desensitization with subactivating concentrations of nicotine (Marks et al, 2010), so any differences in function observed after 24-hour nicotine across the a4 variants are due to effects conferred by the variants themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine crosses cell membranes very quickly (Fig. 9), and in some cells, it can accumulate to much higher than ambient concentrations (e.g., in negatively charged compartments within X. laevis oocytes) (Jia et al, 2003;A. Kuryatov, V. Gerzanich, and J. Lindstrom, unpublished data).…”
Section: Fig 4 ␣4␤2mentioning
confidence: 95%
“…This probably reflects irreversible desensitization of some of the AChRs (Gentry and Lukas, 2002;Gentry et al, 2003). An alternate explanation would be that nicotine, which had accumulated within the cells, partitioned out slowly, sustaining the AChRs in a reversibly desensitized state (Jia et al, 2003).…”
Section: Fig 2 Activation By Acetylcholine Of ␣4␤2mentioning
confidence: 99%
“…The reporter mutation approach was not used to monitor changes in the function of ␣4␤2 nAChRs because the leftward shifts in the ACh concentration-response curves caused by the reporter mutation or by changes in subunit composition would overlap, making it difficult to separate both effects (compare curves in Fig. 2 (Jia et al, 2003;López-Herná ndez et al, 2004) the ACh responses of oocytes expressing ␣4␤2 nAChRs were depressed by long-term exposure to 5 M nicotine. Therefore, before recordings, oocytes were maintained for 4 h in 15 ml of nicotine-free Barth's solution in a Petri dish (one oocyte per Petri dish) placed on a rotating platform.…”
Section: Methodsmentioning
confidence: 99%